ANALISIS PENANAMAN KARAKTER SABAR MELALUI KEGIATAN CIRCLE TIME PADA SISWA KELAS I SEKOLAH DASAR - Khusnia, Yun Ni’matul; Purnamasari, Veriliana; Kurnia, Evivalen Arnis (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study explores the effectiveness of circle time activities in instilling the character of patience in Grade 1 A students at SD Bukit Aksara. Using qualitative research methods through observation, interviews, and documentation, it was found that circle time, conducted three times in each session, serves as a platform for character education. The activity begins to prepare students, continues in the middle of the lesson to condition them before and after breaks, and ends with reflection. Its main focus is teaching patience through the practice of waiting for turns, listening attentively, and respecting others' opinions. The Grade 1 A teacher, Mrs. Ika Kristina, reported that students demonstrated patient behavior, such as waiting for their turn and listening to peers without interruption. Moreover, this activity also supports the development of students' social and emotional skills, such as empathy and communication abilities. These findings align with previous studies showing that the BCCT (Beyond Centers and Circle Time) model positively impacts children's character development. This study emphasizes that circle time not only enhances social interaction in the classroom but also builds strong character and interpersonal skills that are beneficial for future challenges.